Performance evaluation of the novel 3D-printed aquatic plant-microbial fuel cell assembly with Eichhornia crassipes - Mel Patrick D. Malinis; Herna Jones F Velasco; Kristopher Ray Pamintuan (International Journal of Renewable Energy Development, 2023)
Plant-Microbial Fuel Cells (PMFCs) are a sustainable derivative of fuel cells that capitalizes on plant rhizodeposition to generate bioelectricity. In this study, the performance of the novel 3D-printed aquatic PMFC assembly with Eichhornia crassipes as the model plant was investigated. The design made use of 1.75 mm Protopasta Conductive Polylactic Acid (PLA) for the electrodes and 1.75 mm CCTREE Polyethylene Terephthalate Glycol (PETG) filaments for the separator. Three systems were prepared with three replicates each: PMFCs with the original design dimensions (System A), PMFCs with cathode-limited surface area variations (System B), and PMFCs with anode-limited surface area variations (System C). The maximum power density obtained by design was 82.54 µW/m2, while the average for each system is 26.99 µW/m2, 36.24 µW/m2, and 6.81 µW/m2, respectively. The effect of variations on electrode surface area ratio was also examined, and the results suggest that the design benefits from increasing the cathode surface area up to a cathode-anode surface area ratio of 2:1. This suggests that the cathode is the crucial component for this design due to it facilitating the rate-limiting step. Plant health was also found to be a contributing factor to PMFC performance, thereby suggesting that PMFCs are an interplay of several factors not limited to electrode surface area alone. The performance of the novel PMFC did not achieve those obtained from existing studies. Nevertheless, the result of this study indicates that 3D-printing technology is a possible retrofit for PMFC technology and can be utilized for scale-up and power amplification.